Peningkatan Keterampilan Membaca Intensif Melalui Penggunaan Strategi Directed Reading Thinking Actiity (DRTA) pada Siswa Kelas 4 SD Negeri 1 Bengkalis Kecamatan Bengkalis Kabupaten Bengkalis - Rosdaliana Rosdaliana (Akademika: Jurnal Keagamaan dan Pendidikan, 2017)
Improving the skills of reading intensively through the use of the strategy Directid Reading Thinking ActIity (DRTA) on the Grade 4 Students of SD 1 Bengkalis District Bengkalis Regency of Bengkalisskilled in reading means able to read and able to understand the content of the reading quickly and accurately. Reading skills obtained a person through the process of continuous training and focused that started since early age without no limit finally. A skills must be trained with an adequate understanding of the theory and use tricks,how, strategy and maximum technique. The ability to read ditumbuh Primary School students need to develop as early as possible.based on the preliminary study obtained the information that the ability to read intensive students in grade 4 SD Negeri 1 Bengkalis District Bengkalis has not satisfied. One of the causes of which are considered most of its influence is the ability of the teacher has not been effective in selecting and implementing the right strategy. The implementation of DRTA strategy is one alternative in the intensive reading. This research in the form of class action research.This research done to know the capacity of students in grade 4 SD Negeri 1 Bengkalis district Bengkalis in intensive reading through the implementation of DRTA strategy. The subject of this research is the grade 4 students of SD 1 Bengkalis district Bengkalis which numbered 22 people. There are two data in this research is data the ability of students in the intensive reading is the primary data and data observation of the activity of the teachers and students during the learning process that is a secondary data. The technique of data collection is done through test, observation and note the field. The results of this research showed that the use of DRTA strategy in teaching reading can improve the ability of students in the intensive reading. This can be seen in the development of the ability of students to understand the reading material through enabling skemata students increased on stage prabaca. The success of the action is in good qualification (B). On the stage when the students to read it looks more enthusiastic and termotIasi in learning. The students have difficulties in answering questions about the contents of the new reading only passage, become more helped with the implementation of DRTA strategy. The success of the action is in good kalsifikasi (B). Finally the development of the understanding of the students in the post-stage read the results of fortifying shows that through class discussions can increase the ability of students tounderstand the reading material. The success of the action is on the good classification (B).